Impact of compounded drugs on the caregivers' burden of home therapy management in pediatric palliative care: A descriptive study. (March 2023) - Burlo, Francesca; Zanon, Davide; Passone, Eva; Toniutti, Maristella; Ponis, Giuliano; Barbi, Egidio; Taucar, Valentina; De Zen, Lucia
Background: Children with medical complexity need complex assistance, that considerably affects caregivers' quality of life. They often need multiple medications, with a consequent relevant risk of errors or poor compliance. Galenic (or compounded) drugs are blended in the pharmacy's laboratory worldwide according to different rules and tailoring the patient's needs. While their use may sometimes simplify these therapies, little is known about parents' attitude about this issue. Aim: This study aimed at investigating the complexity of the daily therapy management and exploring the parents' opinions about galenic compounds. Design: Parents were interviewed by using a structured questionnaire. Setting: Children followed by the Pediatric Palliative Care Network in Friuli Venezia Giulia, Italy, were included from November 2021 to April 2022. Those diagnosed with malignancies were excluded, since therapies are mainly administered through a central venous catheter. Results: Thirty-four parents were interviewed. Fourteen patients took drugs orally, one via nasogastric tube (NGT), 18 via gastrostomy, and one orally + NGT. The mean number of drugs taken every day was six (2–14), in mean 10 (3–18) administrations, that overall required a mean of 44 (8–180) minutes to be delivered. Twenty-eight parents used galenic compounds, and 24 reported relevant advantages, because of a ready-to-use and safe formulation. Conclusions: The therapy management of children with medical complexity relies on parents. Galenic compounds may improve both patients' and caregivers' quality of life, either in terms of shorter time of administration or smaller risk of errors. Therefore, their use should be encouraged worldwide, according to the different reference rules.